Pengaruh Kepuasan Kerja, Affective Commitment, Continuance Commitment, dan Normative Commitment terhadap Turnover Intention Karyawan Grand Palace Hotel Malang - Kevin Luhika Sakila (Ekonomi Bisnis, 2019)
ABSTRACT  Sakila, Kevin Luhika. 2018. The Influence of Job Satisfaction, Affective Commitment, Continuance Commitment, and Normative Commitment to Employee Intention Turnover Grand Palace Hotel Malang. Sarjana's Thesis, Department of Management, Faculty of Economics, Universits Negeri  Malang. Advisor: Lohana Juariyah, S.E., M.Si  KEY WORDS: Job Satisfaction, Affective Commitment, Continuance Commitment, Normative Commitment, Employee Turnover Intention The hospitality industry is one of the industries that often experience employee turnover problems. Basically, to know the factors causing someone out of the company is very difficult. Before the employee decides to leave the organization, it first appears the intention of the employee to leave the organization (turnover intention). Job satisfaction, affective commitment, continuance commitment, and normative commitment are the four factors that influence employee turnover intention. This study aims to (1) to describe descriptive job satisfaction, affective commitment, continuance commitment, normative commitment and turnover intention of Grand Palace Hotel employees (2) to find out whether job satisfaction, affective commitment, continuance commitment and normative commitment have negative and significant influence against employee turnover intention Grand Palace Hotel.This type of research uses a quantitative approach with multiple linear regression analysis. The population in this study are all employees of Grand Palace Hotel with contract status of 45 respondents. Sampling technique using total sampling technique. Methods of data collection using open and closed questionnaires.From the data analysis, the results obtained that, employee job satisfaction in the high category or satisfied; affective commitment of employees into high or good category; continuance commitment of employee into category enough or good enough; employee normative commitment is high or good category; and employee turnover intention included in the category enough. The result of analysis using SPSS shows that: (1) Job satisfaction has negative and significant effect to employee intention turnover, meaning H1 is accepted; (2) Affective commitment has a negative but insignificant effect on employee turnover intention, meaning H2 is rejected; (3) Continuance commitment has a negative and significant effect on employee intention turnover, meaning that H3 is accepted; (4) Normative commitment negatively and significantly affect employee intention turnover, meaning H4 accepted.The suggestion given by the researcher to the Grand Palace Hotel is as follows: (1) pay attention to employee's job satisfaction level, especially on the attitude that is not satisfied with salary, promotion, and coworkers relationship (2) emotional employees by providing motivation, understanding of the hotel's mission vision, ownership and sense of love towards the organization, increasing employees' self-confidence that they are right to lose if leaving the hotel because other organizations are no better, maintaining an already high normative commitment employee response to items that indicate a lack of sense of debt to the organization (3) and then for employee intent turnover, it is necessary to consider the direction and provision of self-confidence in employees is a business that can dampen the intentions of employees to find another job. In subsequent research to retest or re-examine whether it is true that affective commitment has an insignificant negative effect on the turnover intention of other hotel employees.